2015
DOI: 10.1111/gcb.13078
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis reveals global hotspots for marine debris ingestion by sea turtles

Abstract: 30Plastic marine debris pollution is rapidly becoming one of the critical environmental 31 concerns facing wildlife in the 21 st century. Here we present a risk analysis for plastic 32 ingestion by sea turtles on a global scale. We combined global debris distributions 33 based on ocean drifter data with sea turtle habitat maps to predict exposure levels to 34 debris. Empirical data from necropsies of deceased animals were then utilised to 35 assess the consequence of exposure to plastics. We modelled the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 53 publications
2
103
0
Order By: Relevance
“…Compared to other studies that use a simulation-based approach to describe the impact of spatial debris distributions on species such as sea turtles (Schuyler et al, 2016) or sea birds , we used high-resolution operational models to identify the variability of floating litter concentrations induced by hydrodynamic features. Using real data from aerial surveys performed in the Channel, the Atlantic and the Mediterranean regions, Darmon and collaborators (Darmon et al, in press) identified the exposure areas of loggerhead sea turtles (Caretta FIGURE 9 | Fin whale habitat maps (Feeding Habitat Occurrence) (A1-A3) and simulated distribution of microplastics (items/m2) (B1-B3) in north-western Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies that use a simulation-based approach to describe the impact of spatial debris distributions on species such as sea turtles (Schuyler et al, 2016) or sea birds , we used high-resolution operational models to identify the variability of floating litter concentrations induced by hydrodynamic features. Using real data from aerial surveys performed in the Channel, the Atlantic and the Mediterranean regions, Darmon and collaborators (Darmon et al, in press) identified the exposure areas of loggerhead sea turtles (Caretta FIGURE 9 | Fin whale habitat maps (Feeding Habitat Occurrence) (A1-A3) and simulated distribution of microplastics (items/m2) (B1-B3) in north-western Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to review and model the incidence of plastic ingestion by marine organisms (e.g. Schuyler et al, 2015;Wilcox et al, 2015) depend critically on negative as well as positive records of plastic ingestion. We strongly encourage researchers to report all records of organisms checked for debris ingestion, irrespective of whether any debris is found or not.…”
Section: Discussionmentioning
confidence: 99%
“…Ocean circulation models can further be used to identify where oceanic accumulation zones are most likely to occur. Coupling such tools and approaches with species distribution maps and other ecological information, we can combine disparate data types to predict or identify hotpots of risk to taxa or geographic regions of interest (Schuyler et al, 2013(Schuyler et al, , 2015Wilcox et al, 2015Wilcox et al, , 2016. We can also identify movement pathways or trajectories , identify hotspots, and develop scenario analysis tools to identify potential sources and sinks.…”
Section: Needed Improvementsmentioning
confidence: 99%
“…Dynamically modeling the risk or impacts becomes critically important not only for individuals and populations, but also for marine species that are exposed to multiple threats to survival and persistence. Identifying key geographic regions and taxa at higher or lower threat from marine plastics (e.g., Schuyler et al, 2015;Wilcox et al, 2015) can provide a useful lever to drive policy.…”
Section: Needed Improvementsmentioning
confidence: 99%